Fine Distributed Moderating Material with Improved Thermal Stability Applied to Enhance the Feedback Effects in SFR Cores - Bruno Merk (Science and Technology of Nuclear Installations)
The use of fine distributed moderating material to enhance the feedback effects and to reduce the sodium void effect in sodium-cooled fast reactor cores is described. The influence of the moderating material on the fuel assembly geometry, the neutron spectrum, the feedback effects, the power and burnup distribution, and the transmutation performance is given. An overview on possible materials is provided and the relationship between hydrogen content and thermal stability is described. A solution for the problem of the limited thermal stability of primarily proposed hydrogen-bearing moderating material ZrH1.6 is developed by the use of yttrium-mono-hydride. The similarity in the effects reached by ZrH and YH is demonstrated by comparison calculations. The topic is closed by an overview on material properties, manufacturing issues, experience in fast reactors, and a comparison of raw material costs.